Procyanidin B2 ameliorates endothelial dysfunction and impaired angiogenesis via the Nrf2/PPARγ/sFlt-1 axis in preeclampsia - Lei Liu; Rencheng Wang; Ran Xu; Yuening Chu; Weirong Gu (Elsevier, 2022)
Preeclampsia is a severe complication of pregnancy characterised by variable degrees of placental malperfusion. A growing body of evidence indicates that soluble endoglin and soluble fms-like tyrosine kinase-1 (sFlt-1) play important pathophysiological roles in preeclampsia, causing endothelial dysfunction, hypertension, and multiorgan injury. A drug that is safe in pregnancy and inhibits placental sFlt-1 and soluble endoglin secretion would be an attractive treatment strategy for preeclampsia. Procyanidin B2, a bioactive food compound, has been reported to exert multiple beneficial functions. Placental explant cultures in vitro are useful for studying tissue functions including release of secretory components, pharmacology, toxicology, and disease processes. The reduced uterine perfusion pressure (RUPP) rat model has been widely used as a model of preeclampsia. We aimed to investigate the effect of procyanidin B2 on preeclampsia via using placental explant cultures and RUPP rat model. In this study, we demonstrated that procyanidin B2 reduced soluble endoglin and sFlt-1 secretion from human umbilical vein endothelial cells (HUVECs), primary trophoblasts, and placental explants from preeclamptic pregnancies. Moreover, procyanidin B2 alleviated endothelial dysfunction and impaired angiogenesis induced by sFlt-1, including increasing the migration, invasion and angiogenesis of endothelial cells and decreasing the expression of vascular cell adhesion molecule-1 (VCAM-1) and leukocyte adhesion on HUVECs. In addition, procyanidin B2 promoted nuclear factor erythroid 2-related factor 2 (Nrf2) nuclear accumulation and induced peroxisome proliferator-activated receptor γ (PPARγ) expression in primary placental tissues and endothelial cells. Importantly, Nrf2 specifically binds to the PPARγ promoter region (-1227/-1217) and enhances its transcriptional activity. Procyanidin B2 inhibits sFlt-1 secretion via the Nrf2/PPARγ axis. In the RUPP rat model of preeclampsia, procyanidin B2 attenuated RUPP-induced maternal angiogenic imbalance, hypertension and improved placental and foetal weight. Taken together, our results demonstrate that procyanidin B2 inhibits sFlt-1 secretion and ameliorates endothelial dysfunction and impaired angiogenesis via the Nrf2/PPARγ axis in preeclampsia. Procyanidin B2 may be a novel therapeutic agent for treatment of preeclampsia.